Brain training improves endurance performance - Marcora, S. M.; Staiano, W.; Merlini, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: It has been demonstrated that mental fatigue (MF) has a negative impact on perception of effort and endurance performance (EP) (Marcora et al., 2009). Therefore, interventions that increase resistance to MF should reduce perception of effort and improve EP. The aim of this study was to test the efficacy of Brain Endurance Training (BET), a new kind of brain training specifically designed to improve EP. BET is based on the hypothesis that systematic repetition of mentally fatiguing tasks would increase resistance to MF and, thus, improve EP. Methods: 28 healthy and physically active males were randomly assigned to two different training groups: BET and control. Both groups trained on a cycle ergometer for 60 min at 65% of VO2max. Whilst cycling, the BET group (N = 14) performed a mentally fatiguing task on a computer (60 min of the AX-CPT task). The control group (N = 14) was not involved in any mentally fatiguing task whilst cycling. Both groups trained three times a week for 12 weeks. Peak power output (PPO) and VO2max (incremental test), and EP (time to exhaustion [TTE] test at 75% of current PPO) were measured at baseline (pre-test), after six weeks of training (mid-test) and after 12 weeks of training (post-test). Rating of perceived exertion (RPE) was measured every minute during the TTE test. Results: VO2max increased similarly in both the BET group (pre 40 ± 5; mid 48 ± 6; post 52 ± 7 ml/kg/min) and the control group (pre 40 ± 6; mid 48 ± 6; post 52 ± 6 ml/kg/min) (p < .001). However, TTE increased significantly more in the BET group (pre 27 ± 10 min; mid 38 ± 11 min; post 51 ± 15 min) than in the control group (pre 19 ± 6 min; mid 24 ± 7 min; post 30 ± 13 min) (p < .05). Analysis of covariance to adjust for baseline differences in TTE revealed an even larger improvement in the BET group (113%) compared to the control group (43%) (p < .01). This ubstantial effect of BET on TTE was associated with a significant reduction in RPE (p < .05). Discussion: The results of this study provide experimental evidence that the addition of BET to a standard aerobic training program is highly effective in reducing perception of effort and improving EP. Future studies should investigate the brain adaptations underlying the positive effects of BET, and its efficacy in elite endurance athletes for which BET may provide a novel training stimulus without overloading the musculoskeletal system.